Quantification of the effect of air traffic on terminal precinct ground traffic and the corresponding ground traffic effect on kerbside and parking infrastructure requirements at O.R. Tambo international airport - Adam, Fatima (Department of Civil Engineering, 2024)
The sharp increase in travel demand at ORTIA In recent years has been translated into frequent parking supply and kerbside pickup/drop-off bay shortages, particularly during peak periods. This often results in long delays and Increased frustration amongst those using these facilities. In an attempt to solve the termlnal precinct congestion problems currently experienced at O.R. Tambo International Airport (ORTIA), a need exists to understand parking and kerbside drop.aff/plck-up bay demand, so that Infrastructure Investment corresponds to this demand. In light of this, the objective of this study is twofold, namely: To find a relationship between travel demand created by flight activity and terminal precinct ground traffic generation, specifically terminal frontage road and parking facility demand. This relationship should define: The number of person trips produced and attracted by flight activity; and The mode-split and occupancy of these trips, so as to determine the number of vehicle trips per mode produced and attracted by the flight activity. This will, in tum, provide an indication of the demand for parking and kerbside facilities; and To utilise the established parking and kerbside traffic demand Information to determine the corresponding landslde infrastructure required to satisfy the terminal precinct traffic demand at ORTIA. The Infrastructure requirements of this study speclfically alms to determine: The number of kerbside pick-up and drop.aff bays required by the various modes utilising the frontage roads; and the number of public parking bays required by air travellers and visitors to the terminals.